Korai kötődés, anya-gyermek interakciók és autizmus spektrum zavar - Mándoki, Noémi (Magyar Pedagógia, 2018)
The theme of this synthesizing study is autism spectrum disorder and early attachment. The study explores whether the risk factors connected to attachment quality jeopardize the secure attachment of children with autism spectrum disorder. Such risk factors may be: child temperament, maternal mental health or sensitive behaviour. Certain temperament and behaviour characteristics on the child side may help, others, either directly or indirectly may jeopardize the formation of secure attachment and reciprocity. Certain early and later behavioral differences in social skills or in nonverbal communication sharply differentiate ASD from other developmental disorders. Another important issue from the point of view of the study’s theme is how the increased stress level and mental burden of the mother influence mother-child reciprocity and the sensitive and responsive maternal behaviour. It seems that the parents of ASD children are able to react responsively and sensitively to the child’s signs in spite of the increased anxiety and high level of stress. ASD does not jeopardize forming secure attachment relationship that much as one would expect based on the characteristics of developmental disorder and other risk factors. At the same time the quality of attachement might be expressed differently and ASD children may show atipic bonding behaviour. They less securely attach to their caregiver than non ASD children and autism has only partial effect on attachement security. More narrow the applied diagnostic criteria, more severe the intellectual disability the stronger these effect on the quality of attachement (increase the probability of formation of insecure attachement).